ALCOHOLISM PHONIDA GIGAR AGREES MORPHOMETRIC PARAMETERS - Ҳамроев Худойшукур Нутфиллоевич (Web of Journals Publishing, 2024)
In recent decades, scientists have devoted more time to the study of the mechanisms of action of extreme influences, such as alcohol poisoning, on the internal organs. Some diseases, based on quantitatively assessed morphological changes in internal organs, have eliminated the methods of differential diagnosis of the cause of death under the influence of a combination of substances on the body, each of which can lead to death. It is emphasized that often extremely strong loads can begin their potential dynamogenic effect not in one data, but in a certain time interval, unknown in advance, during each stress injury. A review of the literature shows that the available data on the structural and functional state of the liver in laboratory rats is sparse. Based on the above, we set out to study the age-related medical care of the liver in laboratory rats.
Keywords: Liver, alcohol, morphological changes.